Analysis of different fixed and flexible dielectric materials on microstrip patch antenna for ISM band applications. Issue 1 (February 2020) - Prasad, M; Ramya, P; Poongodi, C; Prasanna, R; Raj Kamal, S; Praveen Kumar, M
Abstract: Recently, advancement in wearable technologies, one challenging improvement is textile antenna. The most requirements of textile antennas are dielectric materials which include fabric substrate and the structure of the antenna. The characteristics of the antenna depends on the substrate material. The dielectric value of the fabric material can be calculated from the operating frequency of patch antenna. In this paper the micro strip patch antenna is designed for ISM band applications. The main objective of this paper is to design and compare the performance of the micro strip patch antenna on different fixed and flexible dielectric material like FR-4, RT DUROID 6010, Polystyrene, Teflon, Quartz, Cotton, Alumina, Polyester with different constant in terms of gain, return loss, radiation patterns The proposed antenna operate at the resonant frequency 2.45GHz(ISM band) with low return loss and high gain and directivity.The size of the designed antenna has been also miniaturized.